Perceptions of Sports Science Students at Yogyakarta State University on Interest and Motivation to Learn SCUBA Diving - Muhamad Nanang Solikhin; Sumaryanti Sumaryanti; Sulistiyono Sulistiyono; Fauzi Fauzi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
The scope of sports as stated in Indonesian Law no. 3 of 2005, concerning the National Sports System includes three pillars, namely sports education, recreational sports, and achievement sports. Students' interest and motivation to study types of fun recreational sports and students develop competencies/skills that can enable future professional opportunities to become an important part of the consideration in diving at the Faculty of Sports Science, Yogyakarta State University. The method used in this research is a survey using a questionnaire. The questionnaire used includes a closed-end questionnaire, in which the respondent chooses the alternative answers that have been provided. The research respondents were 19 students who volunteered in the diving learning model test. Research on student perceptions of diving is very much needed as a basis for understanding diving as a whole. The results of the study obtained the Perception value of students of the Faculty of Sports Science, Yogyakarta State University about learning the sport of Scuba Diving